Indywidualizacja nauczania i uczenia się – otwarte formy pracy w gimnazjum oraz w kształceniu akademickim (action research) - Karpeta-Peć, Beata (Neofilolog, 2017)
The aim of this article is the theoretical and empirical analysis of the issue of individualization of learning and teaching foreign languages with reference to open forms of work at foreign language lessons and in academic study. The empirical part is the report on the author’s own educational studies of open forms of work, conducted at lower-secondary school and in the academic context (at the pilot-phase). The starting point for the analysis is methodological background of educational and language teaching research. The conclusions may serve as the inspiration for further research in this field.